Growth‐associated protein 43 and progressive epilepsy in cortical dysplasia. (11th June 2014) - Ying, Zhong; Najm, Imad; Nemes, Ashley; Pinheiro‐Martins, Ana Paula; Alexopoulos, Andreas; Gonzalez‐Martinez, Jorge; Bingaman, William
Abstract Objective To investigate growth‐associated protein 43 (GAP‐43), a marker for axonal growth and synaptic plasticity, as potential substrate for progressive epilepsy and potential predictor of postsurgical seizure outcome in patients with focal cortical dysplasia (FCD). Methods GAP‐43 immunohistochemistry was performed on cortical specimens from 21 patients with FCD: 12 with FCD type II (IIA or IIB) and nine with FCD type IA. Twenty normal anterior temporal lobe specimens from patients with mesial temporal lobe epilepsy due to hippocampal sclerosis (mTLE/HS) were used as controls. Semiquantitative analysis of GAP‐43 staining patterns was performed. Additionally, GAP‐43 immunoblotting was performed on resected tissue from three patients with FCD type IIA/B; GAP‐43 protein levels in electroencephalography‐verified epileptic, and distal nonepileptic, areas were compared within each patient. Two outcome categories were used: completely seizure free (Engel IA) versus not seizure free. We examined the relationship of GAP‐43 scores with epilepsy duration and seizure‐free outcome for each of the three pathologies. Results Within‐patient GAP‐43 expression is selectively increased in the epileptic as compared to nonepileptic cortex. GAP‐43 immunoreactivity (IRs) patterns were seen on the cell surface and tubular punctate structures intercellularly only in FCD cortex. Higher GAP‐43 scores were correlated (P < 0.0001) with longer epilepsy duration only in FCD IIA/B. Lower GAP‐43 scores were associated with better surgical outcome in the same group. No such relationship was observed in FCD IA. Interpretation GAP‐43 proteins are not only associated with intrinsic epileptogenicity but may be markers of progressive epilepsy and predictors of postoperative seizure outcome in patients with pharmacoresistant epilepsy due to FCD IIA/B.